37.2: Efficiency Improvement of Fluorescent Blue Device by Molecular Orientation of Blue Dopant. Issue 1 (1st July 2013) - Ogiwara, Toshinari; Ito, Hirokatsu; Mizuki, Yumiko; Naraoka, Ryo; Funahashi, Masakazu; Kuma, Hitoshi
Abstract The relationship between molecular shape of fluorescent blue dopants (BDs) and molecular orientation factor was studied. BDs with larger ovality showed higher orientation factor and higher EQE over 10% in a fluorescent blue device. Impedance spectroscopy, transient EL spectroscopy and optical simulation results highly indicate that such high EQE is originated mainly from the optical effect of horizontal‐aligned BDs. Furthermore, a higher EQE of 11.5% at a current density of 10mA/cm2 was successfully achieved by modifying molecular structure of BD.